Collaborative Strategies in Efforts to Increase the Innovation Index in Cimahi City Government - Hilda Nurul Anggraeni; Nita Nurliawati; Ely Sufianti; Ono Taryono (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
The regional innovation index (IID) is a collection of regional innovations that spur innovation practice. IID encourages local governments to make innovative policies for the welfare of their people. Involvement between actors is needed in the implementation of regional innovations. Collaboration can overcome organizational in implementing innovation. The assessment of the regional innovation index among regional apparatus is still not optimal. The problem faced is the decline in the value of the regional innovation index in 2020. The purpose of this research is to analyze the collaboration between the regional innovation index. This research uses descriptive qualitative method. The data were obtained through interviews, observations and document studies. Data analysis techniques were carried out through data reduction, data presentation, and conclusions. Test the validity of the data using the credibility test, transferability test, dependability test, and confirmability test. The researchers used the collaborative governance model from Ansell and Gash (2007). Formulate research strategies using SWOT analysis techniques. The results of the study indicate that collaboration is still not optimal. To overcome this problem, the researcher proposes strategies including technical training, socialization of regional innovation, collaboration with LAN RI,, strengthening regional innovation policy regulations, and building cooperation Regional Work Units.